Sosialisasi Daur Ulang Sampah Plastik Menjadi Paving Blok di Desa Bojongloa Kecamatan Rancaekek Kabupaten Bandung - Maha, Yohana Gole (Jurnal Pengabdian Tri Bhakti, 2023)
The problem that occurs in Bojongloa village is scattered garbage due to the absence of a garbage collection site or garbage bank, attention from local residents and village officials is very minimal. Therefore, the author's purpose in holding a socialization of recycling plastic waste into paving blocks is to utilize plastic waste around to become a work of art and additional income for the people of Bojongloa village, especially in RW 16. In this study, the author's focus is to help the community find solutions to various problems, one of which is plastic waste management. Based on the results of surveys, interviews, and observations conducted on the people of Bojongloa village, especially in RW 16 and Karang Taruna RW 16, Rancaekek District, that public concern for waste management is very minimal and there are many piles of plastic waste that can have negative impacts on health and disrupt the sustainability of environmental functions, both residential areas, rice fields, and rivers. To reduce the volume of plastic waste that is not managed properly, efforts are made to utilize plastic waste to make Paving Blocks. The method used in plastic waste management efforts is by providing socialization and assistance to the community about the plastic waste management process. The solution provided by the author was successfully implemented in Bojongloa village, especially in RW 16.